How successful people think change your thinking, change your life - Maxwell, John C. (New York Hachette, 2009)
Gather successful people from all walks of life-what would they have in common? The way they think! Now you can think as they do and revolutionize your work and life!
Unabridged
Keywords: Success-Psychological aspects